Role of the quality of education in national economy of the republic of uzbekistan - Kabulov, A; Sidikova, F (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Quality of education is acquiring primary importance as it is a central problem of education system throughout the world today. Growingaccessibility of higher education contributes to the development and activation of human resources of the country, rise of regions and realization of youth rights to higher education. Therefore, the article shows the reasons that reduce the quality of education, suggests ways to reform and improve a system of higher education in the republic